Garland-Structured Bi2o2co3@Ni(Oh)2 as a Battery-Type Electrode for High-Performance Electrochemical Energy Storage Device Applications - Radhalayam, D (Elsevier Ltd, 2024)
Electrochemical energy storage (EES) systems are gaining prominence as a solution to the issue of conventional energy supply while also reducing environmental pollutants. Electrode morphological engineering is one approach to improving EES device performance in terms of specific capacity, energy density, and power density. Bismuth compounds are interesting because of their enormous reserves and high theoretical capacity for use as anodes in aqueous alkaline batteries and supercapacitors. Here, a hydrothermal technique embeds Ni(OH)2 nanosheets into Bi2O2CO3 flakes to alter their morphology. This creates garland structures with an equal molar ratio of Bi to Ni sources. In conjunction with the mesopores of the distinctive shape, the interconnected petals offer excellent electron and ion transit channels. Furthermore, the tightly integrated garland structures enhance the stability of the crystal structure, which may improve the electrochemical stability. It has a higher specific capacity of 232.87 mAh g−1 at a current density of 0.5 A g−1 and is very stable during cycling (remaining 85.12 % of the initial capacity at 1 A g−1 after 5000 cycles). This suggests that Bi2O2CO3@Ni(OH)2 garland structures are a viable electrode material for energy storage devices. © 2024